Financing for development series: The financial crisis and developing countries - Peter Wolff (Deutsches Institut für Entwicklungspolitik (DIE), 2008)
Developing countries will be severely affected by the financial crisis. Emerging economies are already suffering from capital outflows and a sudden credit stop. In many low-income countries the financial crisis is exacerbating the ongoing food price crisis, which has already had disastrous effects on the poor. Given the limited fiscal space for compensatory measures in developing countries, industrialised countries are being asked to mobilise a fraction of their financial rescue packages to compensate for the collateral damage to developing countries caused by the crisis. The development finance institutions, backed by the assets of industrialised countries, should play a strong countercyclical role by providing credit in areas from which commercial players have retreated, thus helping to finance social safety nets as well as long-term investments in agriculture, infrastructure, and sustainable energy.
Keywords: 330